Analisis makna onomatope dalam manga “Gyakuten Saiban" karya Kenji Kuroda - Agus Wahyudi; Eva Amalijah (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
The purpose of this research is to describe the types and contextual meanings of the onomatopoeias found in the comic "Gyakuten Saiban". The steps in the data collection process started from selecting a comic entitled Gyakuten Saiban, reading dialogue dialogues in the comic, collecting data by recording the onomatopoeias contained in the comic, sorting data based on the type of classification, to compiling 5 data tables according to the type of classification. The results of this research were 35 onomatopoeic words consisting of 11 giongo words imitating the sounds of inanimate objects, 2 giseigo words imitating the sounds of living things, 3 gitaigo words denoting the state of inanimate objects, 2 gijougo words denoting the state of the human heart or feelings. and 17 giyougo words which state the state or behavior of living things. The onomatopoeia that is often used is giyougo which states the state or behavior of living things.